Virtual endocasts of Eocene Paramys (Paramyinae): oldest endocranial record for Rodentia and early brain evolution in Euarchontoglires - Bertrand, Ornella C. (Proc Biol Sci, 2016)
Understanding the pattern of brain evolution in early rodents is central to reconstructing the ancestral condition for Glires, and for other members of Euarchontoglires including Primates. We describe the oldest virtual endocasts known for fossil rodents, which pertain to Paramys copei (Early Eocene) and Paramys delicatus (Middle Eocene). Both specimens of Paramys have larger olfactory bulbs and smaller paraflocculi relative to total endocranial volume than later occurring rodents, which may be primitive traits for Rodentia. The encephalization quotients (EQs) of Pa. copei and Pa. delicatus are higher than that of later occurring (Oligocene) Ischyromys typus, which contradicts the hypothesis that EQ increases through time in all mammalian orders. However, both species of Paramys have a lower relative neocortical surface area than later rodents, suggesting neocorticalization occurred through time in this Order, although to a lesser degree than in Primates. Paramys has a higher EQ but a lower neocortical ratio than any stem primate. This result contrasts with the idea that primates were always exceptional in their degree of overall encephalization and shows that relative brain size and neocortical surface area do not necessarily covary through time. As such, these data contradict assumptions made about the pattern of brain evolution in Euarchontoglires.